Clinical features, radiological findings, and prognostic factors for primary intracranial chordoid meningioma - Jie, Danyang; Liu, Zhiyong; He, Wenbo; Wang, Shumin; Teng, Haibo; Xu, Jianguo (Frontiers in Neurology, 2022)
Objectives Chordoid meningioma (CM) is an infrequent histologic subtype of meningiomas. Owing to its low occurrence, the subtype has been rarely described. Our subject was to explore the clinical features, radiological findings and prognostic factors for primary intracranial chordoid meningioma. Methods We reviewed the medical records and follow-up information of 34 cases with primary intracranial CM, which had been surgically treated and histologically diagnosed, among 7950 patients with meningiomas who had received surgical resection at the Department of Neurosurgery, West-China Hospital of Sichuan University, from January 2009 to December 2021. Results In our institution, the proportion of primary intracranial CM in overall meningiomas was 0.43%. The median diagnosis age was 47 (ranging from 12 to 74) and the gender ratio (male to female) was 2.1:1. For radiological features, CM was observed to be with a high rate of heterogeneous enhancement, more skull base and ventricular localization, high occurrence of cystic degeneration and dural tail sign. Simpson Grade I to II were categorized as gross total resection (GTR), which was achieved in 22 patients, and Level III to IV (subtotal resection, STR) was achieved in 12 patients. 11 patients received postoperative adjuvant radiotherapy (RT). The follow-up duration ranged from 4 to 157 months after operation. The progression rate was 20.7% and the median of PFS was 38 months. Accepting adjuvant radiotherapy and achieving GTR were correlated with better survival for prognosis. Conclusions CM is a rare subtype of primary intracranial meningiomas. It mainly involved the adult patients and did not show significant sex predilection compared with meningiomas in general. There were some radiological features of CM in our series: localization predilection for skull-base and ventricle, high occurrence of cystic degeneration, irregular shape and unclear interface, more heterogeneous enhancement and higher occurrence of dural tail sign. For treatment, Gross total resections (GTR) are recommended to prolong survival of CM patients. Besides, postoperative adjuvant radiotherapy was proved to be related to prognosis.